Hubungan Pengetahuan dan Jarak Tempat Tinggal Masyarakat terhadap Pemanfaatan Pelayanan Puskesmas di Huta Sidodadi, Pematang Silampuyang - Nur Masdalifah; Eka SR. Sihombing; Hiban Auzi; Meylinda Sinaga (Jurnal Minfo Polgan, 2025)
The purpose of this study was to examine the relationship between the level of public knowledge about ARI and preventive measures taken in the work area of ​​the UPTD Puskesmas Raya (Regional Health Center) in 2025. This study employed a quantitative method with an analytical approach using a cross-sectional design. Data were collected by distributing questionnaires to 97 respondents selected using a purposive sampling technique. Data analysis was performed using the chi-square test. The study findings showed that the majority of respondents had sufficient knowledge (45.4%) and moderate preventive behavior (50.5%). A significant relationship was found between the level of public knowledge about ARI and the preventive measures taken (p < 0.05). Based on the results, it can be concluded that the higher a person's knowledge, the more optimal their preventive behavior. Therefore, this study recommends the importance of improving public health education programs to reduce the incidence of ARI in the UPTD Puskesmas Raya's work area.